Association Between Dynamic Trends of Functional Disability and Poverty Among People Aged 45 and Over - Liao, Hui; Yan, Chaoyang; Ma, Ying; Wang, Jing (Frontiers in Public Health, 2022)
Background: The disability problem has become prominent with the acceleration of the global aging process. Individual disability is associated with economic conditions and contributes to family poverty. As disability will change over a long period of time and may even show distinct dynamic trends, we aimed to focus on activities of daily living (ADL) and classify functional disability trends. Moreover, we aimed to highlight and analyze the association between functional disability trends and economic conditions and explore the influencing factors. Materials and Methods: A total of 11,222 individuals who were 45 years old or older were included in four surveys conducted by the China Health and Retirement Longitudinal Study in 2011, 2013, 2015, and 2018. Samples were analyzed after excluding those with missing key variables. The latent class growth model was used to classify the ADL trends. Two binary logistic regressions were established to observe the association between the ADL trends and follow-up economic conditions or catastrophic health expenditure trends. Results: ADL trends of older adults were classified into improving (25.4%), stabilizing (57.0%), and weakening ADL (17.6%). ADL trend was associated with follow-up poverty (p = 0.002) and catastrophic health expenditure trends (p < 0.001). Compared with the improving ADL trend, the stabilizing ADL may have a negative influence on individuals’ economic conditions (OR = 1.175, 95%CI = 1.060 – 1.303). However, a stabilizing ADL trend was less likely to bring about catastrophic health expenditures (OR = 0.746, 95%CI = 0.678 – 0.820) compared with an improving ADL trend. Conclusion: The improvement of functional disability would make the medical expense burden heavier but would still be beneficial to the prevention of poverty. A significant association was found between socioeconomic factors and poverty. Preventing the older adults from developing disability and illness, improving the compensation level of medical insurance, and optimizing the long-term care insurance and the primary healthcare system can potentially contribute to the prevention of poverty. Meanwhile, focusing on people who are poor at early stages, female, middle-aged, low-educated, and in rural areas is important.